RNA-Seq Reveals Extensive Transcriptional Response to Heat Stress in the Stony Coral Galaxea fascicularis - Hou, Jing; Xu, Tao; Su, Dingjia; Wu, Ying; Cheng, Li; Wang, Jun; Zhou, Zhi; Wang, Yan (Frontiers in Genetics, 2018)
Galaxea fascicularis, a stony coral belonging to family Oculinidae, is widely distributed in Red Sea, the Gulf of Aden and large areas of the Indo-Pacific oceans. So far there is a lack of gene expression knowledge concerning this massive coral. In the present study, G. fascicularis was subjected to heat stress at 32.0 ± 0.5 oC in the lab, we found that the density of symbiotic zooxanthellae decreased significantly; meanwhile apparent bleaching and tissue lysing were observed at 10 h and 18 h after heat stress. The transcriptome responses were investigated in the stony coral G. fascicularis during heat bleaching using RNA-seq. A total of 42,028 coral genes were assembled from over 439 million reads. Gene expressions were compared at 10 and 18 hours after heat stress. The significantly upregulated genes found in the Control_10h vs. Heat_10h comparison, presented mainly in GO terms related with DNA integration and unfolded protein response, and for the Control_18h vs. Heat_18h comparison, the GO terms include DNA integration. In addition, comparison between groups of Control_10h vs. Heat_10h and Control_18h vs. Heat_18h revealed that 125 genes were significantly upregulated in common between the two groups, whereas 21 genes were significantly downregulated in common, all these differentially expressed genes were found to be involved in stress response, DNA integration and unfolded protein response. Taken together, our results suggest that high temperature could activate the stress response at the early stage, and subsequently induce the bleaching and lysing through DNA integration and unfolded protein response, which are able to disrupt the balance of coral-zooxanthella symbiosis in the stony coral G. fascicularis.